Performance of spreading sequences in CDMA system - Lin, Zinan. (2008)
This thesis proposes to use the recently introduced Unified Complex Hadamard Transform (UCHT) as the spreading sequences for CDMA systems. A new expression for the UCHT matrices has been derived and a new method of generating UCHT sequences has been developed for use with CDMA systems.